Effect of atmosphere on the electrical properties of TiO2-SnO2 varistor systems - Sousa, V. C.; Cassia-Santos, M. R.; Barrado, C. M.; Bomio, MRD; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Kluwer Academic Publ, 2004)
This work illustrates the advancement of research on TiO2-based electroceramics. In this work will be presented that the addition of different dopants, as well as thermal treatments at oxidizing and inert atmosphere, influences of the densification, the mean grain size and the electrical properties of the TiO2-based varistor ceramics. Dopants like Ta2O5, Nb2O5, and Cr2O3 have an especial role in the barrier formation at the grain boundary in the TiO2 varistors, increasing the nonlinear coefficient and decreasing the breakdown electric field. The influence of Cr'(Ti) is to increase the O' and O'(2) adsorption at the grain boundary interface and to promote a decrease in the conductivity by donating electrons to O-2 adsorbed at the grain boundary. In this paper, TiO2 and (Sn,Ti)O-2-based studies of polycrystalline ceramics, which show a non-linear I-V electrical response typical of low voltage varistor systems are also presented. All these systems are potentially promising for varistor applications. (C) 2004 Kluwer Academic Publishers.